SISTEM INFORMASI PENGOLAHAN DATA NILAI BERBASIS WEB PADA SMA SWASTA VALENTINE DISKI - Delvi Natalina Br Tarigan; Rimbun Siringoringo; Resianta Perangin-angin (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2021)
The web-based student value data processing system is one of the systems that give the student’s associated value and activation information online, so it can reinforce the speed and quality of the student’s assessment. The problem with data processing at the high school private valentine diski is currently in manual. This research is aimed at quickly establishing value information systems in check, logging and computerized. In addition, using web-based data processing information can be accssed at any time. This application USES xampp as a server for system designers and mysql as database. The login menu design consists of the homeroom teachers, admin, principal and students have separate access when it will open applications so that the program’s security is protected. The system works the insertion of data, the storing of data, and the processing of data assessments presented by the school. The study has produced a value data processing system that helps performance from both the administration and the homeroom teacher, thus facilitating the use of well-conveyed value processing processes. In addition, system interfaces are implemented according to existing report CARDS so that systems can be used easily and generate accurate value calculations.